(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2015)
The article analyzes the current classification of the types of abbreviations and acronyms used in the English radio ATIS messages. Analysis of different types of abbreviations and acronyms led to the conclusion that, along with lots of acronyms in the English phraseology of radiotelephony elliptical and initially-elliptical abbreviations are widespread.